Characteristics of Precipitating Storms in Glacierized Tropical Andean Cordilleras of Peru and Bolivia. Issue 2 (4th March 2017) - Perry, L. Baker; Seimon, Anton; Andrade-Flores, Marcos F.; Endries, Jason L.; Yuter, Sandra E.; Velarde, Fernando; Arias, Sandro; Bonshoms, Marti; Burton, Eric J.; Winkelmann, I. Ronald; Cooper, Courtney M.; Mamani, Guido; et al.
Abstract : Precipitation variability in tropical high mountains is a fundamental yet poorly understood factor influencing local climatic expression and a variety of environmental processes, including glacier behavior and water resources. Precipitation type, diurnality, frequency, and amount influence hydrological runoff, surface albedo, and soil moisture, whereas cloud cover associated with precipitation events reduces solar irradiance at the surface. Considerable uncertainty remains in the multiscale atmospheric processes influencing precipitation patterns and their associated regional variability in the tropical Andes—particularly related to precipitation phase, timing, and vertical structure. Using data from a variety of sources—including new citizen science precipitation stations; new high-elevation comprehensive precipitation monitoring stations at Chacaltaya, Bolivia, and the Quelccaya Ice Cap, Peru; and a vertically pointing Micro Rain Radar—this article synthesizes findings from interdisciplinary research activities in the Cordillera Real of Bolivia and the Cordillera Vilcanota of Peru related to the following two research questions: (1) How do the temporal patterns, moisture source regions, and El Niño-Southern Oscillation relationships with precipitation occurrence vary? (2) What is the vertical structure (e.g., reflectivity, Doppler velocity, melting layer heights) of tropical Andean precipitation and how does it evolve temporally? Results indicate that much of the heavy precipitation occurs at night, is stratiform rather than convective in structure, and is associated with Amazonian moisture influx from the north and northwest. Improving scientific understanding of tropical Andean precipitation is of considerable importance to assessing climate variability and change, glacier behavior, hydrology, agriculture, ecosystems, and paleoclimatic reconstructions.